IFPA meeting 2015 workshop report I: placental mitochondrial function, transport systems and epigenetics. (December 2016) - Bianco-Miotto, T.; Blundell, C.; Buckberry, S.; Chamley, L.; Chong, S.; Cottrell, E.; Dawson, P.; Hanna, C.; Holland, O.; Lewis, R.M.; Moritz, K.; Myatt, L.; et al.
Abstract: Workshops are an important part of the IFPA annual meeting as they allow for discussion of specialized topics. At IFPA meeting 2015 there were twelve themed workshops, three of which are summarized in this report. These workshops covered areas of placental regulation and nutrient handling: 1) placental epigenetics; 2) placental mitochondrial function; 3) placental transport systems.